PENGARUH KONFLIK TERHADAP KOMITMEN ORGANISASIONAL DAN KEPUASAN SERTA KINERJA PEGAWAI SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH I PROVINSI KALIMANTAN BARAT - SUMADI B2043142008 (Equator Journal of Management and Entrepreneurship (EJME), 2017)
The purpose of this study was to examine and analyze the effect of conflict on organizational commitment and satisfaction as well as employee performance Unit Implementation of National Road Region I West Kalimantan Province. Forms of this study was to use an associative with qualitative and quantitative approaches. Collecting data using primary data in the form of questionnaires and interviews and secondary data sourced from National Road Implementing Unit Region I West Kalimantan Province. Sample using a sample census. The sample in this study is the overall spegawai on National Road Implementation Task Force Region I West Kalimantan as many as 49 people.The results of this study indicate that the conflict on organizational commitment and satisfaction as well as employee performance Unit Implementation of National Road Region I West Kalimantan Province. Keywords: Conflict, Organizational Commitment, Satisfaction and Employee Performance.